KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MAN 1 LAMPUNG SELATAN - Hanafi, Hanafi (UNISAN JURNAL, 2023)
Teachers are a component of madrasahs that greatly determine the success of teaching and learning in order to improve the quality of education in madrasahs. Madrasah heads have a strategic role in improving teacher performance. This study aims to find out how the leadership of madrasah heads in improving teacher performance in MAN 1 South Lampung. This research uses qualitative descriptive research methods. Data collection techniques in the form of observations, interviews, and documentation. Data analysis includes data collection, data presentation, and drawing conclusions. The results of the study show that the leadership of the head of MAN I Lampung Selatan has carried out leadership well, including in terms of influencing subordinates with communication to achieve goals, giving orders/tasks, motivating and coordinating teachers in realizing all plans to achieve the vision and mission of the madrasah, as well as creating self-confidence and support among subordinates. This has a significant impact on improving teacher performance in MAN I Lampung Selatan. However, it is undeniable that the performance of MAN I Lampung Selatan teachers still needs to be improved to be more optimal.